INCREASING ENTREPRENEURSHIP KNOWLEDGE IN THE DEVELOPMENT OF CATUR KINTAMANI HERBAL TOURISM VILLAGE MENGWI - I Wayan Ruspendi Junaedi; I Gusti Bagus Rai Utama; Dermawan Waruwu (International Journal of Social Science, 2021)
The covid-19 pandemic declared on March 11, 2020 has affected countries on all continents. Coronavirus 19 began appearing in Wuhan, the capital of China's Hubei province, in December 2019 and spread throughout Asia and the world. In response to the development of information related to Coronavirus Disease 2019 (COVID-19) and also following the advice of the Government of Indonesia, on March 16, 2020, several companies or institutions began to implement the call to work and learn from home as a social distancing movement. The various impacts caused by this pandemic are that many people lose their jobs so that in the current difficult time it is expected that the community is able to creatively carry out all activities from home. The same is true in Chess Village, Kintamani, Bangli. The problem found that (1) Do not have knowledge about entrepreneurship for the youth of Kintamani Chess Village. (2) Do not have an entrepreneurial souvenir product for tourists who visit, especially in making photo frames in bottles in chess villages. To overcome these problems, the objectives of the PKM program are as follows: (1). Socialization and knowledge training on entrepreneurship for the youth of Chess Village, Kintamani. (2) Training in making entrepreneurial souvenir products for visiting tourists, especially in making photo frames in bottles in Catur Village, Kintamani. Methods of implementation of the PKM Program include: initial socialization, training, mentoring, monitoring, evaluation, and sustainability of the program, which is carried out by the service team and assisted by experts and students from Dhyana Pura University. The result is that the Chess Village has knowledge, skills about (1). Entrepreneurship (2). There are entrepreneurial souvenir products for tourists who visit, especially in making photo frames in bottles. The implementing team and each group report the results by means of presentation and documentation. The sustainability of this program is that the community continues to learn and the PKM Undhira team assists the group in improving its well-being.